The Single European Market / Prospects for Economic Integration - Vickerman W. R (Harvester Wheatsheaf, 1992)
A unified introduction to the key economic issues raised by the European Community, the completion of the Single Market and the moves to economic and monetary union. Preface, Economic Integration: An Overview, Location and Transport and Trade, Measuring Regional Competitiveness, The Existing Order: Integration to 1991, Realizing the Single Market, The Impact on Sector, The Impact on Regions, The New Order? Integration to 2001, Bibliography, Index.